THE EFFECT OF PROBLEM BASED LEARNING MODEL USING ANIMATION VIDEO ON STUDENT LEARNING OUTCOMES ON THE HUMAN RESPIRATORY SYSTEM MATERIAL - Silaban, Ramlan; Indrayani, Lisa; Harahap, Fauziyah; Hendro Pranoto; Martina Asiati Napitupulu (Jurnal Ilmu Pendidikan Indonesia, 2025)
The objective of this study is to determine the effect of the Problem Based Learning model assisted by animated videos on science learning outcomes in the topic of the Human Respiratory System among eighth-grade students at SMP Imelda Medan. The population of this research comprised all eighth-grade students at SMP Imelda Medan. The sample classes were selected using random sampling, with two classes chosen as the sample. This study employed a quantitative research method, specifically a quasi-experimental approach with a Pretest-Posttest Nonequivalent Control Group Design. Data collection techniques included pre-research observation, interviews with science teachers of grade VIII, written multiple-choice tests for students, and documentation during the research. Data analysis was conducted using hypothesis testing (one-tailed t-test). These data indicate that the implementation of the Problem Based Learning model assisted by animated videos significantly improves students' learning outcomes of eighth-grade students at SMP Imelda Medan on the topic of the human respiratory system.